Optical Dating of Eolian Dune Sand from the Canadian Prairies - Lian, Olav; Huntley, David; Wolfe, Stephen (Géographie physique et Quaternaire, 2002)
AbstractOptical dating is a well-established method that is used to determine the time elapsed since quartz or feldspar grains were last exposed to sunlight, which usually dates the time elapsed since their burial in a sedimentary deposit. Only a few seconds of direct sunlight are needed to reset the “mineral clock”, making the method ideal for dating the formation of eolian landforms. In this paper we describe how we use violet luminescence that is emitted in response to near-infrared excitation of sand-sized K-feldspar grains to date the time of formation of eolian dunes on the Canadian prairies. Using the multiple-aliquot with thermal transfer correction method, together with a test for sufficient sunlight exposure, and a correction for anomalous fading, we are able to produce accurate optical ages ranging from 150 years to more than 11 ka with precision usually better than 10 % at 2σ. Ages are given for dunes in the Dundurn and Elbow sand hills of south-central Saskatchewan, the climatic significance of which is provided in a paper also in the present volume. Knowledge of when the dunes were stable, and when they were not, is used to help understand the nature and timing of Holocene climate change in the area.